The potential of renewables in the Slovak electricity sector - Kochová, Rebeka; Vlčková, Jana; Bič, Josef; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
The main objective of this bachelor’s thesis is to evaluate the current setting of the energy policy of the Slovak Republic and the potential of increasing the share of renewables in the electricity sector. The energy policy of the Slovak Republic is characterised by a strong reliance on nuclear energy which generates more than 50% of the electricity in the country, and is expected to increase even more in future. The Slovak Republic has set the target for the share of RES on the total energy consumption by 2030 at the level of 19,2%. This goal is seen as modest and the European Commission also views it as unambitious. The analysis shows that there is potential to further increase the use of renewables not only in the electricity sector, but also other sectors like in the heating industry. The potential lies in solar, wind and geothermal energy. However, there are obstacles such as bureaucracy, EIA law or lack of governmental incentives.
Vedoucí práce: Jana Vlčková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses